Experimental analysis of surface roughness in the cutting process of sugar palm fiber reinforced unsaturated polyester composites with laser beam and abrasive water jet cutting technologies - Masoud, Fathi; Sapuan, Salit Mohd; Anuar Mohd Ariffin, Mohd Khairol; Nukman, Yusoff; Bayraktar, Emin (King Mongkut's University of Technology North Bangkok, 2022)
This research aims to investigate the effects of the input parameters on the surface roughness as output parameters of CO2 laser and abrasive water jet (AWJ) machining technologies utilized in cutting sugar palm fiber reinforced unsaturated polyester (SPF-UPE) composite of three specimen thicknesses. The objective of this study is to collect data involve the optimal parameters of these technologies regarding the surface roughness response. The motive was to avoid defects arising use in the conventional cutting techniques. In the AWJ technique, stand-offdistance, traverse speed, and water pressure were chosen as variable input parameters to optimize the surface roughness, whereas laser power, traverse speed, and gas pressure were the variable input parameters in the CO2 laser cutting technique. Taguchi’s approach was used to estimate the input parameter’s levels that produce the best surface roughness. Analysis of variation (ANOVA) was used to determine the contribution of every single input processing parameter to the effect on the surface roughness response. Good surface roughness responses could be attained by applying the optimum input parameters determined in this study. The experimental results of the current research provide practical data for the cutting of SPF-UPE composites with CO2 laser and AWJ machining techniques, and the findings can be used as a good starting point for the testing of other similar composites under the same cutting conditions